THE TEACHERS’ KNOWLEDGE ABOUT NEW PRESCHOOL CURRICULUM - Abdul Halim Masnan; Muhammad Haziq Mohd Sharif; Masayu Dzainuddin; Hafsah Taha; Mohd Mokhzani Ibrahim; Asmayati Yahaya; Che Nidzam Che Ahmad; Saipolbarin Ramli; Rosfizah Md Taib; Mazlina Che Mustafa; Nurul Shakila Ahmad Abdul Wahab, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The new preschool curriculum in Malaysia is known as the National Preschool Standard-Based Curriculum (NPSC) (Revised 2017) requires knowledgeable, well-skilled and more experienced teachers in its implementation. This study aimed to identify the teachers’ level of knowledge about the new preschool curriculum from the private sector. A total of 269 private kindergarten teachers in a Selangor district were randomly selected as respondents. They were asked to respond to the questionnaire and the data collected were then analysed descriptively. Overall findings showed that the majority of those private kindergarten teachers had a High Level of knowledge about the new preschool curriculum. The demographic details also revealed that the majority of private kindergarten teachers had more years of experience, but half of them did not have any professional qualifications and not involved in professional development. In conclusion, these findings explained that though half of the private kindergarten teachers do not meet the professional criteria, they have good knowledge of NPSC (Revised 2017). This study has suggested that further research relating to the preschool curriculum is needed and provides supportive information to the Ministry of Education (MOE) and local private kindergartens.